Rancang Bangun Media Pembelajaran Pengenalan Hewan Dalam Bahasa Inggris Pada Siswa Sekolah Dasar Berbasis Mikrokontroler - J, Shafa Adillah; Retno Devita, Retno Devita; Putra, Ondra Eka; Rianti, Eva (Jurnal Teknik dan Teknologi Tepat Guna, 2025)
The development of digital technology is driving innovation in education, particularly in creating interactive and engaging learning media for elementary school students. This research aims to design and build a microcontroller-based English learning media for first-grade elementary school students. This system integrates an Arduino Mega 2560 as the main controller, connected to various components such as touch sensors, RFID, push buttons, LEDs, LCDs, and a DFPlayer module to support interaction and learning. This system offers two main features: visual and audio animal name recognition, and an interactive quiz mode that tests students' understanding by providing multiple-choice questions based on the story. When students touch an animal image, the system displays the animal's name in English and Indonesian, along with pronunciation sounds and descriptions. The quiz can be accessed using an RFID card, and students answer using the touch sensor. Feedback is displayed via LEDs and audio from the speaker. Test results indicate that the system operates well and is responsive, and is able to increase students' interest in English lessons. This research is expected to provide an alternative solution for enriching foreign language learning methods at the elementary level with a simple yet effective technological approach.